Delays Analysis Of TRANSKO Tawes 11.3 DWT Mooring Boat Development Project Based On Risk Management - Imam Pujo Mulyatno; Samuel; Feri Adi Mukhlisin; Syaiful Tambah Putra Ahmad (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
In shipbuilding projects, it is often the case that the project completion time exceeds the planned target time. Risk is an important factor in estimating the project schedule. If risk occurs in a project, it is certain that the project duration will increase. Therefore, risk analysis and mitigation are needed in the risk management of shipbuilding projects. The case study in this research is the 11.3 DWT TRANSKO Tawes mooring boat construction project owned by PT Pertamina Trans Kontinental which is experiencing delays. With data in the form of the project main schedule, risk analysis uses Primavera Risk Analysis software integrated with the Monte Carlo method to analyze risks to the schedule and provide an estimate of the exact project completion time. By randomly decreasing the uncertainty variable for 201 iterations, the results show that the percentage value of project delays is 11.38% of the target project construction duration of 167 days so that the project is estimated to experience a maximum delay of 19 days from the planned target duration so that the project is completed in 186 days or 1 day longer than the actual duration of the project which is completed in 185 days. In the TRANSKO Tawes 11.3 DWT mooring boat construction project, 12 risks were obtained that affected the project with details of 3 high category risks, 2 medium category risks, and 7 low category risks. As for the actual duration of the project, there is an increase in productivity compared to the duration of the simulation results, which is 0.0001 DWT/mandays.